Desain dan Simulasi Bidirectional DC-DC Converter untuk Penyimpanan Energi pada Sistem Fotovoltaik - Armadilla Sukma Pratiwi; Syechu Dwitya Nugraha; Epyk Sunarno (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2020)
In this paper, a bidirectional DC-DC converter for energy storage in the photovoltaic system has been designed and simulated on MATLAB Simulink. The bidirectional DC-DC converter can work in two modes, charge and discharge mode. The energy storage system will work to store energy into the battery when the power generation capacity is higher than load demand. Then, the energy stored in the battery will be used for the DC bus supply when the power generation capacity is lower than the load demand. To get a constant voltage on the high voltage side (DC bus voltage) and a constant current on the low voltage side (charging current), a PI controller is used. Simulations were carried out with 1,000 W/m2 irradiation to get the power generation higher than the load demand (charge mode) and 200 W/m2 irradiation to get the power generation lower than the load demand (discharge mode) with constant temperature of 25 °C. The test result shows that a bidirectional DC-DC converter can work in charge and discharge modes, which is shown by battery charging currents and the increase or decrease in battery voltage.